Know your neighbor : Jake M. Lujan (The Raton Daily Range Raton, New Mexico, 1964)
Newspaper Article on Jake M. Lujan and his military career and family.
Master list item #: 16
File location is in the Raton File Cabinet
Keywords: Lujan, Jake M; Wilson, Woodrow; Hoover, Herbert; Martinez, Delores; Martinez, Juan C; Martinez, Juanita; Lujan, Jake Jr; Lujan, Billy; Lujan, Donald; Lujan, Bonnie; Lujan, Louis; Lujan, Ernest; Lujan, Alfonso; Lujan, Carlos; St. Joseph's Academy; Trinidad Catholic; Clayton American Legion Post; Veterans of Foreign wars; Disabled American Veterans; Miner's Hospital; Lake Motor Company; Smith Grocery Store; Colorado Interstate Gas Company; Local History; Biography; Life and Customs; World War I -- U.S. Soldier; Presidential honor guard; Sergeants -- Military -- World War I; Education; Rancher; Family; Raton, New Mexico; Des Moines, New Mexico; France; Cimarron, New Mexico; Trinidad, Colorado; Clayton, New Mexico; El Paso, Texas; Albuquerque, New Mexico; Camp Kearny, California; San Diego, California; Cimarron County, Oklahoma; Highland Park, Illinois; Masterson, Texas; Santa Fe, New Mexico; San Leandro, California